Wound healing after transoral angiolytic laser surgery for early glottic carcinoma. (8th September 2018) - Tracy, Lauren F.; Hron, Tiffiny A.; Van Stan, Jarrad H.; Burns, James A.
Abstract : Objectives/Hypothesis: Wound healing after transoral angiolytic laser surgery for early glottic carcinoma was analyzed to identify factors influencing healing and clinical significance of persistent granulation tissue. Study Design: Retrospective review. Methods: A retrospective review of 100 consecutive patients undergoing endoscopic angiolytic laser surgery for T1 and T2 glottic carcinoma was performed. Patients with prior radiation or incomplete data were excluded. Postoperative endoscopic images were analyzed for time to healing, size and location of wound, and presence of granulation tissue. Three blinded, independent raters graded wound appearance and presence of granulation tissue. Results: Seventy‐nine patients healed without need for intervention at a median of 3.5 months. Two patients had office‐based ablation of granulation without biopsy and healed. The remaining 19 patients had biopsy for granulation tissue. Wounds that underwent biopsy at >3 months were more likely to contain carcinoma (5/6 patients, 83%) than wounds that were biopsied <3 months (2/13 patients, 15%) ( P = .004). Presence of granulation significantly correlated with resection involving anterior commissure ( P = .01), > 75%vocal fold length ( P = .006), and depth into muscle ( P = .001). Delayed healing (>3 months) correlated with T2b tumors ( P = .02), depth into ligament ( P = .002) and anterior commissure involvement ( P = .04). T1a carcinomas more commonly healed in <3 months ( P = .005). Conclusions: Many vocal fold wounds heal completely within 3.5 months after angiolytic laser surgery for early glottic carcinoma. Larger and deeper wounds are more likely to heal with granulation tissue. Granulation can resolve without surgical intervention; however, granulation present > 3 months warrants biopsy due to increased risk of malignancy. Level of Evidence: 4 Laryngoscope, 129:435–440, 2019